2016
DOI: 10.1016/j.jemep.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

“I think we’ve got too many tests!”: Prenatal providers’ reflections on ethical and clinical challenges in the practice integration of cell-free DNA screening

Abstract: Background The recent introduction of cell-free DNA-based non-invasive prenatal screening (cfDNA screening) into clinical practice was expected to revolutionize prenatal testing. cfDNA screening for fetal aneuploidy has demonstrated higher test sensitivity and specificity for some conditions than conventional serum screening and can be conducted early in the pregnancy. However, it is not clear whether and how clinical practices are assimilating this new type of testing into their informed consent and counselli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…In addition to increased education for providers, allocating more time to counselling may improve informed choice. Studies of women and clinicians identified strong consensus that consultations did not provide sufficient time for thorough counselling [30, 48, 87]. Some women found that their counselling session was too short for the volume of information they were presented with, and as a result felt overwhelmed [67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to increased education for providers, allocating more time to counselling may improve informed choice. Studies of women and clinicians identified strong consensus that consultations did not provide sufficient time for thorough counselling [30, 48, 87]. Some women found that their counselling session was too short for the volume of information they were presented with, and as a result felt overwhelmed [67].…”
Section: Discussionmentioning
confidence: 99%
“…What are their preferences for the facilitation of informed choice? There is a burgeoning amount of empirical literature [4448] about the challenges of informed decision making about NIPT. The purpose of this review is to bring together this collection of primary research to comment on women’s perspectives, experiences, and preferences for informed decision making about NIPT.…”
Section: Introductionmentioning
confidence: 99%
“…Our participants’ enthusiasm for an expanded offer of NIPT contrasts with existing ethics literature detailing the numerous reasons why an expanded offer may not be prudent. One caution widely present in the literature is that an expanded offer of NIPT to all women challenges the ideal of informed decision-making because of persistent misunderstandings of accuracy, a lack of time for counselling, sparse availability of counselling specialists, and the potential that the procedurally-simple test could be easily routinized [ 15 , 41 , 42 , 48 , 51 , 62 65 ]. Additional arguments in the literature against expanding the offer of NIPT to all women include: the evidence base in normal-risk women was established only recently, the private-pay nature of the test may discriminate in access, quality assurance measures are not widely in place, and primary prenatal care providers may not have the time or expertise available to offer NIPT more widely [ 15 , 41 , 42 , 48 , 62 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have identified deficiencies in the current model that we use to counsel patients providing possible targets for future improvement in the knowledge translation process. For example, in a recent study looking at the US prenatal providers’ reflections on cfDNA screening, providers felt they did not have enough time to adequately counsel and educate patients and that they needed additional education about cfDNA screening which would preferably come from sources like professional societies, labs, and publications [ 27 ]. Palomaki et al recently assessed the experience of the obstetrical care providers, as well as the 2691 women that cfDNA screening was offered to [ 28 ].…”
Section: Discussionmentioning
confidence: 99%